You can't win by avoiding difficult conversations. Issue 4 (2nd May 2017) - Patton, Bruce
Abstract : Purpose: In business, the failure to engage difficult conversations productively can prevent winning in the market and invite the competition to forge ahead. This study aims to identify areas in business where avoiding difficult conversations can put winning out of reach and present guidelines for handling difficult conversations in these domains. Design/methodology/approach: This is a conceptual paper that presents guidelines on how to manage difficult conversations effectively. Findings: This study shows how to manage difficult conversations with regards to the areas of compensation, performance, strategy and implementation. Originality/value: This paper catalogs sources of lost value. Furthermore, this study outlines what is needed to capture such value, and briefly explains the principles for how to transform an organization to build such capability as a core competence.